2020
DOI: 10.1002/jmor.21297
|View full text |Cite
|
Sign up to set email alerts
|

Tail regeneration in a cephalochordate, the Bahamas lancelet,Asymmetron lucayanum

Abstract: Lancelets (Phylum Chordata, subphylum Cephalochordata) readily regenerate a lost tail. Here, we use light microscopy and serial blockface scanning electron microscopy (SBSEM) to describe tail replacement in the Bahamas lancelet, Asymmetron lucayanum. One day after amputation, the monolayered epidermis has migrated over the wound surface. At 4 days, the regenerate is about 3% as long as the tail length removed. The re‐growing nerve cord is a tubular outgrowth of ependymal cells, and the new part of the notochor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Table 1 reviews the various names applied to cephalochordate fibroblasts (all from the genus Branchiostoma) and shows how a consensus to use the term "fibroblast" eventually emerged. The present SBSEM study demonstrated that, like Branchiostoma, Asymmetron has fibroblasts; those of the latter genus were too few to have been noticed previously by light microscopists (Andrews, 1893;Holland & Somorjai, 2021). In the present study, we found fibroblasts were relatively rare-only 20 of them were detected in the reconstructed region (Figure 2a,b).…”
Section: Fibroblastssupporting
confidence: 49%
“…Table 1 reviews the various names applied to cephalochordate fibroblasts (all from the genus Branchiostoma) and shows how a consensus to use the term "fibroblast" eventually emerged. The present SBSEM study demonstrated that, like Branchiostoma, Asymmetron has fibroblasts; those of the latter genus were too few to have been noticed previously by light microscopists (Andrews, 1893;Holland & Somorjai, 2021). In the present study, we found fibroblasts were relatively rare-only 20 of them were detected in the reconstructed region (Figure 2a,b).…”
Section: Fibroblastssupporting
confidence: 49%
“…It is likely that lobopodia provide much of the motive force for the migration of epidermal cells over the wound surface. These lobopodia are evidently in direct contact with the cut tissues at the amputation surface (Figure 2b, asterisk) because transmission electron microscopy (N. D. Holland & I. M. L. Somorjai, unpublished…”
Section: Resultsmentioning
confidence: 99%
“…The present study concerns tail regeneration in a small, tropical cephalochordate, the Bahamas lancelet ( Asymmetron lucayanum ), a species that regenerates rapidly and with close synchrony from one animal to the next. Holland and Somorjai (2021) recently described tail regeneration in this lancelet by light microscopy and serial blockface electron microscopy; however, they focused mainly on the internal tissues (celomic mesothelium, notochord and dorsal nerve cord) and paid relatively little attention to the epidermis. Here, we use conventional scanning electron microscopy ( SEM ) for a more detailed look at the lancelet epidermis during tail regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…The method to prepare and image serial block face electron micrographs has been described in detail elsewhere 126 . Hearts from 9 months old male animals from each group were perfused with Ringers Solution containing xylocaine (0.2mg/ml) and heparin (20 units/ml) for 2 minutes at 35°C, before being fixed by perfusion using 0.15M cacodylate buffer (pH 7.4) containing 2% formaldehyde and 2.5% glutaraldehyde (Electron Microscopy Sciences) as well as 2mM CaCl 2 at 35°C for 5 minutes.…”
Section: Methodsmentioning
confidence: 99%